TPU Estimation for Bathymetric LiDAR - M. Pfennigbauer; A. Haring; U. Riegl; A. Spitzer (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2025)
A tool for Total Propagated Uncertainty (TPU) estimation is presented, as implemented feature of a bathymetric LiDAR processing software. The algorithm of the TPU Estimator is based on an approach alternative to existing methods. The concept of the novel approach is described, compared with and validated against an established tool. Two examples from different coastal surveys document the application of TPU estimation and allow to observe systematic tendencies of the results. We discuss potential for further improve-ment and consider how to embed TPU estimation into a user interface to generate expressive deliverables as part of hydrographic survey quality verification. Finally, we give an outlook for possible use of LiDAR TPU estimation apart from a-posteriori quality control and outline further development projects.